Tailoring polymer composites for critical thermal applications: a review on fibers, additives, coatings, aerogels, test methodologies - G., Sakthi Balan; S., Aravind Raj; Shahar, Farah Syazwani; Hameed Sultan, Mohamed Thariq (Taylor and Francis Group, 2023)
The properties of fiber-reinforced polymer composites are diminished when exposed to high temperatures. Despite high-grade fibers, additives, and fillers, the polymer matrix is thermally unstable. Numerous studies are conducted to modify thermos and thermoset polymers in order to increase their thermal stability, thermal degradability, and flammability. The thermal properties of a composite are determined by the percentages of additives, fibers, coatings, and fabrication methods. This review goes into detail about developing and testing high-temperature polymer composites, which will be useful for both beginners and experts. At high temperatures, nano-ceramic particles like graphene, diamonds, glass powders, mica powders, and corundum improve polymer thermal stability and mechanical properties. Fuel cell electrodes, ultra-capacitors, and lightning hoists may employ these composites.